A Tutorial into Practical Capacity and Mass Balancing of Lithium Ion Batteries. Issue 12 (22nd August 2017) - Kasnatscheew, Johannes; Placke, Tobias; Streipert, Benjamin; Rothermel, Sergej; Wagner, Ralf; Meister, Paul; Laskovic, Isidora Cekic; Winter, Martin
Abstract : In a lithium ion battery, balancing of active materials is an essential requirement with respect to safety and cycle life. However, capacity oversizing of negative electrodes is associated with decrease of specific energy/energy density. In this work, the required trade-off between maximized specific energy and minimized risk of lithium plating is thoroughly investigated by evaluating underlying potential/voltage curves. The adjustment of targeted state of charge (SOC) for both, positive and the negative electrode, can be achieved by intentional selection of only two parameters: negative/positive electrode active mass ratio and charge cutoff voltage. For investigation and controlling reasons, specific charge capacity reveals to be a simple but effective tool to indirectly predict electrode potentials. While cell kinetics/overvoltage are influenced by both electrodes, specific capacity losses are affected by a single electrode. The latter only correlate with negative electrode's BET surface area as long as specific capacity losses of negative electrodes are higher compared to positive electrodes. Based on these insights, a more systematic performance and safety optimized handling of the trade-off between specific energy and safety risk can be realized.